Abbreviated protocol for breast MRI: Are multiple sequences needed for cancer detection?. Issue 1 (January 2015) - Mango, Victoria L.; Morris, Elizabeth A.; David Dershaw, D.; Abramson, Andrea; Fry, Charles; Moskowitz, Chaya S.; Hughes, Mary; Kaplan, Jennifer; Jochelson, Maxine S.
Highlights: Abbreviated breast MR demonstrates high sensitivity for breast carcinoma detection. Time to perform/interpret the abbreviated exam is shorter than a standard MRI exam. An abbreviated breast MRI could reduce costs and make MRI screening more available. Abstract: Objective: To evaluate the ability of an abbreviated breast magnetic resonance imaging (MRI) protocol, consisting of a precontrast T1 weighted (T1W) image and single early post-contrast T1W image, to detect breast carcinoma. Materials and methods: A HIPAA compliant Institutional Review Board approved review of 100 consecutive breast MRI examinations in patients with biopsy proven unicentric breast carcinoma. 79% were invasive carcinomas and 21% were ductal carcinoma in situ. Four experienced breast radiologists, blinded to carcinoma location, history and prior examinations, assessed the abbreviated protocol evaluating only the first post-contrast T1W image, post-processed subtracted first post-contrast and subtraction maximum intensity projection images. Detection and localization of tumor were compared to the standard full diagnostic examination consisting of 13 pre-contrast, post-contrast and post-processed sequences. Results: All 100 cancers were visualized on initial reading of the abbreviated protocol by at least one reader. The mean sensitivity for each sequence was 96% for the first post-contrast sequence, 96% for the first post-contrast subtraction sequence and 93% for the subtraction MIP sequence. Within each sequence, there was no significant difference between the sensitivities among the 4 readers ( p  = 0.471, p  = 0.656, p  = 0.139). Mean interpretation time was 44 s (range 11–167 s). The abbreviated imaging protocol could be performed in approximately 10–15 min, compared to 30–40 min for the standard protocol. Conclusion: An abbreviated breast MRI protocol allows detection of breast carcinoma. One pre and post-contrast T1W sequence may be adequate for detecting breast carcinoma. These results support the possibility of refining breast MRI screening protocols.